Can Anthropometry and Body Composition Explain Physical Fitness Levels in School-Aged Children? - Chih-Yu Hsu; Liang-Sien Chen; I-Jen Chang; Wei-Ching Fang; Sun-Weng Huang; Rong-Ho Lin; Steve Wen-Neng Ueng; Hai-Hua Chuang (MDPI AG, 2021)
Physical fitness (PF) is closely related to various health outcomes and quality of life among children. However, the associations between anthropometry, body composition (BC), and PF are not fully elucidated. This cross-sectional study aimed to investigate the associations between demographic metrics (age, sex), anthropometric measures (body mass index z-score (BMI z-score) waist/height ratio (WHtR)), BC parameters (body-fat percentage (BF%), muscle weight), and PF levels (800-m run, sit-and-reach, 1-min sit-ups, standing long jump) in school-aged children. Continuous variables were dichotomized by median splits. The results of 180 girls and 180 boys (mean age: 10.0 ± 0.7 years; mean BMI z-score: 0.366 ± 1.216) were analyzed. Multivariable linear regressions revealed that BF% (regression coefficient (B) = 3.4, 95% confidence interval (CI) = 2.5-4.3) was independently correlated with the 800-m run. Sex (B = 4.6, 95% CI = 3.0-6.3), age (B = 3.1, 95% CI = 1.9-4.3), and BMI z-score (B = −0.7, 95% CI = −1.4-−0.1) were independently related to sit-and-reach. Age (B = 3.3, 95% CI = 2.0-4.7), BF% (B = −0.3, 95% CI = −0.4-−0.2), and muscle weight (B = 0.7, 95% CI = 0.2-1.2) were independently associated with 1-min sit-ups. In addition to demography, anthropometry and BC provided additional information concerning some PF levels in school-aged children. Weight management and PF promotion should be addressed simultaneously in terms of preventive medicine and health promotion for children.